Effectiveness of integrase strand transfer inhibitor-based regimens in HIV-infected treatment-naive individuals: results from a European multi-cohort study. (2nd July 2021) - Rossetti, Barbara; Fabbiani, Massimiliano; Di Carlo, Domenico; Incardona, Francesca; Abecasis, Ana; Gomes, Perpetua; Geretti, Anna Maria; Seguin-Devaux, Carole; Garcia, Federico; Kaiser, Rolf; Modica, Sara; Shallvari, Adrian; et al.
Abstract: Background: INSTIs have become a pillar of first-line ART. Real-world data are needed to assess their effectiveness in routine care. Objectives: We analysed ART-naive patients who started INSTI-based regimens in 2012–19 whose data were collected by INTEGRATE, a European collaborative study including seven national cohorts. Methods: Kaplan–Meier analyses assessed time to virological failure (VF), defined as one viral load (VL) ≥1000 copies/mL, two consecutive VLs ≥50 copies/mL, or one VL ≥50 copies/mL followed by treatment change after ≥24 weeks of follow-up, and time to INSTIs discontinuation (INSTI-DC) for any reason. Factors associated with VF and INSTI-DC were explored by logistic regression analysis. Results: Of 2976 regimens started, 1901 (63.9%) contained dolutegravir, 631 (21.2%) elvitegravir and 444 (14.9%) raltegravir. The 1 year estimated probabilities of VF and INSTI-DC were 5.6% (95% CI 4.5–6.7) and 16.2% (95% CI 14.9–17.6), respectively, and were higher for raltegravir versus both elvitegravir and dolutegravir. A baseline VL ≥100 000 copies/mL [adjusted HR (aHR) 2.17, 95% CI 1.55–3.04, P  < 0.001] increased the risk of VF, while a pre-treatment CD4 count ≥200 cells/mm 3 reduced the risk (aHR 0.52, 95% CI 0.37–0.74, P  < 0.001). Predictors of INSTI-DC included use of raltegravir versus dolutegravir (aHR 3.03, 95% CI 2.34–3.92, P  < 0.001), use of >3 drugs versus 3 drugs (aHR 2.73, 95% CI 1.55–4.79, P  < 0.001) and starting ART following availability of dolutegravir (aHR 0.64, 95% CI 0.48–0.83, P  =   0.001). Major INSTI mutations indicative of transmitted drug resistance occurred in 2/1114 (0.2%) individuals. Conclusions: This large multi-cohort study indicates high effectiveness of elvitegravir- or dolutegravir-based first-line ART in routine practice across Europe.